2021
DOI: 10.1039/d0ta10708e
|View full text |Cite
|
Sign up to set email alerts
|

Constructing sheet-assembled hollow CuSe nanocubes to boost the rate capability of rechargeable magnesium batteries

Abstract: Sheet-assembled hollow CuSe nanocubes are fabricated by a facile template-directed selenation method and exhibit record rate capability among the chalcogenide compounds reported so far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 52 publications
2
46
0
Order By: Relevance
“…Considering the average discharge voltage and the maximum discharge capacity of the FeS 2 cathode at 50 mA g −1 , a gravimetric energy density of 714 Wh kg −1 can be achieved. This value is superior to those of various transition-metal chalcogenide cathodes for RMBs (Figure 2d), [4,[16][17][18][19][20][21][22]33,59,[65][66][67][68][69][70][71][72][73][74][75] indicative of the high-energy performance of the FeS 2 cathode in RMBs. In terms of the rate performance, the FeS 2 cathode exhibits a clear capacity decrease with the increase in the current density (Figure S6, Supporting Information).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Considering the average discharge voltage and the maximum discharge capacity of the FeS 2 cathode at 50 mA g −1 , a gravimetric energy density of 714 Wh kg −1 can be achieved. This value is superior to those of various transition-metal chalcogenide cathodes for RMBs (Figure 2d), [4,[16][17][18][19][20][21][22]33,59,[65][66][67][68][69][70][71][72][73][74][75] indicative of the high-energy performance of the FeS 2 cathode in RMBs. In terms of the rate performance, the FeS 2 cathode exhibits a clear capacity decrease with the increase in the current density (Figure S6, Supporting Information).…”
Section: Resultsmentioning
confidence: 95%
“…d) Specific capacity and gravimetric energy density values of the as-prepared FeS 2 cathode and some previously reported metal chalcogenide cathodes in RMBs or hybrid batteries using Mg metal anode. [4,[16][17][18][19][20][21][22]33,59,[65][66][67][68][69][70][71][72][73][74][75] e) Cycling performance of the FeS 2 cathodes at 200 or 400 mA g −1 after activation of 15 cycles at 50 mA g −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Du et al used a simple templatedirected selenization reaction to construct thin-film-assembled hollow CuSe nanocubes at room temperature. 9 Copper selenide Cu 2-…”
Section: Introductionmentioning
confidence: 99%
“…In order to address those issues, many studies have been reported, in which the synthesis of yolk-shell structure hosts is considered to be a potential strategy [8][9][10]. Zhang et al reported a yolk-shell ZnO by using a hydrothermal method, which provided a specific capacity of 1406 mAh g −1 at 0.1C [11].…”
Section: Introductionmentioning
confidence: 99%